1999
DOI: 10.2307/1244325
|View full text |Cite
|
Sign up to set email alerts
|

Are Eco‐Labels Valuable? Evidence From the Apparel Industry

Abstract: Environmentally friendly labels, or eco-labels, have begun appearing on products in the United States and Europe as a manifestation of industry efforts to be perceived as environment-friendly. This study investigates the extent of market valuation of the environmental claims made by apparel manufacturers. Disciplines ABSTRACTUsing U.S. apparel catalogue data, we estimate hedonic price functions to identify market valuation of environmental attributes of apparel goods. We identify a significant and robust prem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
122
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(128 citation statements)
references
References 13 publications
4
122
0
1
Order By: Relevance
“…Local food has been reported to be perceived as having higher quality based on search and experience attributes such as freshness and taste (Byker, Rose, & Serrano, 2010;Chambers, Lobb, Butler, Harvey & Traill, 2007;Dentoni et al, 2009;Goodwin, 2013;Zepeda & Leviten-Reid, 2004). Researchers have reported that consumers believed local food has credence qualities of supporting local producers, supporting the local economy, as well as being environmentally friendly (Darby, Batte, Ernst, & Roe, 2008;Nimon & Beghin 1999;Loureiro, McCluskey, & Mittelhammer, 2002;Thilmany, Bond, & Bond, 2008).…”
Section: Conceptual Model and Literature Reviewmentioning
confidence: 99%
“…Local food has been reported to be perceived as having higher quality based on search and experience attributes such as freshness and taste (Byker, Rose, & Serrano, 2010;Chambers, Lobb, Butler, Harvey & Traill, 2007;Dentoni et al, 2009;Goodwin, 2013;Zepeda & Leviten-Reid, 2004). Researchers have reported that consumers believed local food has credence qualities of supporting local producers, supporting the local economy, as well as being environmentally friendly (Darby, Batte, Ernst, & Roe, 2008;Nimon & Beghin 1999;Loureiro, McCluskey, & Mittelhammer, 2002;Thilmany, Bond, & Bond, 2008).…”
Section: Conceptual Model and Literature Reviewmentioning
confidence: 99%
“…Some of these schemes have been evaluated (e.g. Huang, 1996;Nimon and Beghin, 1999;Johnston et al, 2001;Blend and Ravenswaay, 1999;Teisl et al, 2002;Bjorner et al, 2004), and the studies agree that labeling allows product differentiation that is rewarded in the market. Similar trends have been reported in fair trade product markets, which are also built on ethical concerns (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical work on the topic has yielded limited evidence suggesting the eco-labeling of goods can impact consumer behavior in both stated preference (Loureiro & Lotade, 2005;Loureiro, McCluskey & Mittelhammer, 2001 ) and revealed preference situations (Bjorner, Hansen, & Russell, 2004;Nimon & Beghin, 1999;Teisl, Roe & Hicks, 2002 ). However, surprisingly little work has been done specifically regarding the eco-labeling of services.…”
Section: Introductionmentioning
confidence: 99%